Hospital hospitality: Methodology to measure the perceived quality. maternity of Santa Isabel de Hungría Hospital, Mendoza, Argentina - Aceña, Gabriela Belén (2021)
This research aims to know the perceived quality of the hospitality service of the maternity sector at the Santa Isabel de Hungría Hospital (Guaymallén, Mendoza Province, Argentina). For this, a perception survey was administered to all pregnant women (105) admitted during the period between March 20th and May 20th, 2018. The methodological strategy observed perception surveys, measured with Likert scale. On the one hand, it was concluded that the perception of hospital hospitality quality exceeded 95% satisfaction. The highlights were: communication, accommodation, customer service, security and maintenance. On the other hand, aspects to optimize were detected, especially in relation to delays in the check in, quality and variety of food, some aspects of cleanliness and exaggeration of advertising. This research, conducted from the Degree of Hotel Administration of the Universidad del Aconcagua (Mendoza, Argentina), also aims to make visible unusual labour spaces (schools, hospitals, prisons) for gastronomy and hotel industry professionals.